Development of Chemistry E-Modules Based on Augmented Reality Technology on Hydrocarbon Material - Nur Fitri Fadhilah; Haqqi Annazili Nasution (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2025)
This study aims to develop an Augmented Reality (AR)-based chemistry e-module on hydrocarbon material for use in learning at SMAS Cerdas Murni. Hydrocarbons are considered a challenging topic for students due to their abstract nature. The research adopts a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate), but is limited to theDevelop stage. The development process involved expert validation and user responses to determine the module's feasibility. Validation results showed scores of 90.91% from material experts and 92% from media experts, both categorized as highly feasible. Additionally, teacher responses reached 99% and student responses 91.34%, indicating a strong positive reception. These resultsdemonstrate that the AR-based e-module is not only valid and practical but also effectively supports interactive and innovative learning. It is suitable for enhancing students’ understanding of abstract chemical concepts, particularly hydrocarbons, and shows promise for broader implementation in the classroom.